2015
DOI: 10.1021/acs.joc.5b01677
|View full text |Cite
|
Sign up to set email alerts
|

Enantioselective Synthesis of a Furan Lignan (+)-Sylvone

Abstract: A synthesis of natural tetrahydrofuran lignan (+)-sylvone is achieved starting from methyl allenoate in 5 steps. The synthesis begins from an enantioselective aldol reaction of methyl allenoate with 3,4-dimethoxybenzaldehyde to afford α-addition aldol adduct. Key steps for the synthesis of sylvone include an oxacyclization of the α-hydroxy allenyl adduct followed by a Michael addition of a 1,3-dithiane derivative to establish a sylvone skeleton with suitable stereoselections.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
11
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 55 publications
(26 reference statements)
0
11
0
Order By: Relevance
“…The importance of highly substituted tetrahydrofurans is indicated by the existence of numerous examples of pharmaceutically and biologically interesting tetrahydrofurans/tetrahydrofuran-containing complex molecules, including escitalopram, isosorbide mononitrate, naloxone, and sylvoneall of which possess at least one chiral center …”
Section: Introductionmentioning
confidence: 99%
“…The importance of highly substituted tetrahydrofurans is indicated by the existence of numerous examples of pharmaceutically and biologically interesting tetrahydrofurans/tetrahydrofuran-containing complex molecules, including escitalopram, isosorbide mononitrate, naloxone, and sylvoneall of which possess at least one chiral center …”
Section: Introductionmentioning
confidence: 99%
“…Further transformations including a Michael addition provided the expected natural product (+)-Sylvone A ( 669 ) through a short 5-step reaction sequence. 383 …”
Section: Allenols In Natural Productsmentioning
confidence: 99%
“…Allenes bearing more complex substituents, particularly electron-withdrawing groups, have not been studied to any great extent in the context of metal ion-catalyzed cyclization to heterocycles. Wang studied allenyl silanes, and Lee examined allenyl esters in the context of gold- and copper-catalyzed cyclizations . It was only in 2015 that a silver-catalyzed cyclization of allenes bearing a group 15 electron-withdrawing group was published.…”
mentioning
confidence: 99%
“…Wang studied allenyl silanes, 14 and Lee examined allenyl esters in the context of gold-and copper-catalyzed cyclizations. 15 It was only in 2015 that a silver-catalyzed cyclization of allenes bearing a group 15 electron-withdrawing group was published. Thus, Christov reported that the reaction of phosphonate 1a and phosphine oxide 1b with 5 mol % of AgClO 4 in CH 2 Cl 2 at room temperature afforded dihydrofurans 2a and 2b in 83% and 85% yields, respectively, in under 1 h (Scheme 3).…”
mentioning
confidence: 99%